The Contribution of Motor Vehicle Tax to Local Own-Source Revenue in Banten Province - Muhammad Jamaludin; Intan Puspanita; Selly Haryono (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) IBE Indonesia, 2026)
This study aims to determine the extent of the contribution of Motor Vehicle Tax (PKB) to the Local Own-Source Revenue (PAD) in Banten Province and also to identify the obstacles faced in its collection and management. The data analyzed were obtained from the Local Revenue Agency of Banten Province for the period 2020–2024. The result indicate that PKB remains the largest source of PAD, although its contribution declined from 46.16% in 2020 to 39.56% in 2024. Despite this downward trend, the contribution level remains within the good and fairly good categories. The decline was not driven by a weakening of PKB performance, but rather by the increased contribution of other local revenue sources, such as the Motor Vehicle Title Transfer Fee (BBNKB) and the Motor Vehicle Fuel Tax (PBBKB). The study also identifies several challenges in MVT collection, including low taxpayer compliance, tax arrears, and limitations in administrative systems. Therefore, tax intensification and extensification strategies, enhanced digital services, and improved taxpayer education are required to optimize local tax revenue.